Determinant Of Applying Good Corporate Governance And Tax Management Against Corporate Social Responsibility In Company With Risk Disclosure As Moderated Variabel - Tauperta Siregar; Vinola Herawaty (International Publisher (YAPENBI), 2022)
This study aims to determine the effects of applying good corporate governance and tax management against corporate social responsibility in company with risk disclosure as moderated variabel. The dependent variable in this study is Corporate Social Responsibility, while the independent variable is Good Corporate Governance and Tax Management. Moderating variables using variable Risk Disclosure . The study population was companies listed in Index Sri Kehati in Indonesia. Samples that meet the criteria are as many as 84 companies. With a period of four year of research data. The results of this study demonstrate in partially variable Tax Management no significant effect on Corporate Social Responsibility, while Most of the indicators variables of good corporate governance significant effect on the Corporate Social Responsibility as composition of independent of BOC, Board of commissioners and composition of institutional shareholders. And most of the indicators variables of good corporate governance have no significant effect on the Corporate Social Responsibility as shareholders composition of Managerial, debt policy and the size of the company. Variables simultaneously Good Corporate Governance and Tax Management have a significant effect on Corporate Social Responsibility. Moderation Risk Disclosure is not able to amplify the effect of tax management and good corporate governance of the Corporate Social Responsibility